2000
DOI: 10.1111/j.1749-6632.2000.tb05306.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval Survival of Anocentor nitens Under Simulated Natural Conditions

Abstract: Basic knowledge about the survival of free living stages of ticks is of great importance as a practical tool to improve control methods. For Anocentor nitens there is little information on this subject. Eighty‐four engorged females were incubated at 30°C and 100% relative humidity. After 17 days, groups of 5,500 eggs each were collected and isolated in vials. Age zero was defined as 10 days after eclosion had begun. At this time vials with larvæ were attached to 40 Sorghum halepense plants sowed in clay pots, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The success or failure in egg viability has important biological ramifications, for example, in models that calculate reproductive success of females located at the edges of the distribution range for the species (PRICE, 1977) where not only egg-laying values are considered, but also hatchability and final larvae production. Reproductive capacity of the studied strains provides reference values that should be considered for different uses, as the information generated in the laboratory can be useful to predict behavior in the field (DE LA VEGA; DIAZ, 1996;DE LA VEGA, 2000;OGDEN et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The success or failure in egg viability has important biological ramifications, for example, in models that calculate reproductive success of females located at the edges of the distribution range for the species (PRICE, 1977) where not only egg-laying values are considered, but also hatchability and final larvae production. Reproductive capacity of the studied strains provides reference values that should be considered for different uses, as the information generated in the laboratory can be useful to predict behavior in the field (DE LA VEGA; DIAZ, 1996;DE LA VEGA, 2000;OGDEN et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of thermal constants on the non-parasitic stage of D. nitens was also studied [ 63 , 64 ]. The most favorable climatic conditions for D. nitens in Cuba were temperatures between 26 and 30 °C and 100% of relative humidity [ 63 , 65 , 66 ]. The studies by de la Vega et al [ 32 ] showed that the non-parasitic stage of R. microplus was better adapted to the warm-humid conditions of Cuba than that of D. nitens .…”
Section: Ecophysiology Of Ticks In Cubamentioning
confidence: 99%